Pengembangan Media Pembelajaran Komik Berbasis Digital pada Konsep Sistem Pernapasan Kelas XI: Suatu Penelitian di SMA Negeri 1 Tilamuta - Angreyna Diko; Margaretha Solang; Ilyas Husain (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to develop a digital comic-based learning media on the human respiratory system concept for eleventh-grade students at SMA Negeri 1 Tilamuta. The research employed a Research and Development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed product was tested on a limited scale involving 19 students. Data were collected through expert validation sheets, observation sheets, questionnaires, and learning outcome tests. The results showed that the digital comic learning media achieved a very high level of validity based on media experts, material experts, and biology teachers. The practicality of the media was reflected in the very good implementation of learning activities, increased student engagement, and positive student responses. Furthermore, the effectiveness analysis indicated a significant improvement in students’ learning outcomes, as evidenced by the increase in pretest and posttest scores and an N-Gain value categorized as moderate. These findings indicate that digital comic-based learning media is feasible, practical, and effective for supporting biology learning, particularly in enhancing students’ understanding and learning motivation on the human respiratory system topic.